Anticoagulant Dysfunction of Human Arg352Trp-Activated Protein C Caused by Defective Factor Va Inactivation - Rintelen, Claudia; Yegneswaran, Subramanian; Griffin, John H. (Thrombosis and Haemostasis, 2001)
The dysfunctional mutant R352W-protein C was found in two patients with venous thrombosis. The mutant R352A-protein C was constructed to define the contribution of charge/size of the residue at 352 on protein C (chymotrypsin numbering 187). Compared with wild type-protein C, R352W-protein C showed no difference in activation by thrombin·thrombomodulin or α-thrombin. However, R352W-activated protein C (APC) anticoagulant activity (aPTT assay) was reduced to ~65%. Although the catalytic efficiency of R352W-APC towards the oligopeptide substrate S-2366 was unperturbed, factor Va and R506Q-factor Va were not efficiently inactivated by R352W-APC compared with wild type-APC. R352A-APC showed reduced anticoagulant activity and reduced efficiency in factor Va inactivation and in factor VIIIa-inactivation in the presence of protein S. These observations suggest that the dysfunction of R352W-APC in factor Va inactivation may be one of the mechanisms leading to venous thrombosis in affected patients and that R352 plays an important role in the physiological functioning of APC.
Keywords: Venous thrombosis; protein C deficiency; point mutation; factor Va; dysfunction; anticoagulant